Associations between Phytoestrogens, Glucose Homeostasis, and Risk of Diabetes in Women: A Systematic Review and Meta-Analysis. Issue 6 (21st November 2018) - Glisic, Marija; Kastrati, Natyra; Gonzalez-Jaramillo, Valentina; Bramer, Wichor M; Ahmadizar, Fariba; Chowdhury, Rajiv; Danser, A H Jan; Roks, Anton J M; Voortman, Trudy; Franco, Oscar H; Muka, Taulant
ABSTRACT: Phytoestrogens might have advantageous effects on diabetes in women. We performed a systematic review and meta-analysis to determine the effect of phytoestrogens on glucose homeostasis and the risk of type 2 diabetes (T2D) among women. Randomized controlled trials (RCTs) and prospective observational studies that assessed associations of phytoestrogens (supplementation, dietary intake, or biomarkers) with fasting glucose or insulin, homeostatic model assessment of insulin resistance (HOMA-IR), or with the risk of T2D were included. We identified 18 RCTs ( n = 1687 individuals) investigating the effect of phytoestrogen supplementation on glucose homeostasis and 9 prospective population-based studies ( n = 212, 796 individuals) examining the association between phytoestrogen intake and the risk of T2D. Compared with placebo, phytoestrogen supplementation resulted in improvements in fasting glucose and HOMA-IR: the pooled mean differences of changes were –0.12 mmol/L (95% CI: –0.20, –0.03 mmol/L) and –0.24 mmol/L (95% CI: –0.45, –0.03 mmol/L), respectively. Although there was no significant decrease in insulin concentrations with overall phytoestrogen supplementation, the pooled mean difference in changes was –0.99 pmol/L (95% CI: –4.65, 2.68 pmol/L). However, the results of RCTs varied by type of phytoestrogens: soy-derived isoflavones and genistein improved glucose homeostasis, whereas isoflavone mix and daidzein had no effect or were associated with an adverse glycemic profile. Higher dietary phytoestrogen intake was associated with a 10% lower risk of developing T2D in observational studies (pooled RR: 0.90; 95% CI: 0.85, 0.96; for the highest compared with the lowest quantiles). Results were similar when the analyses were restricted to only medium- and high-quality studies. Overall, phytoestrogens may have a positive influence on glycemia and could be used for diabetes prevention in women. However, for some individual types of phytoestrogens, such as mixed isoflavones, caution is needed in recommending their use in women, because their use could lead to an adverse glycemic profile in women.